PENGARUH KARAKTERISTIK IBU HAMIL DAN PENGETAHUAN TERHADAP SIKAP IBU TENTANG KEHAMILAN RISIKO TINGGI DI WILAYAH KERJA PUSKESMAS TANJUNG BERINGIN KECAMATAN HINAI KABUPATEN LANGKAT TAHUN 2012 - Mova Rita Sitompul; Heru Santosa; Erna Mutiara (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
High-risk pregnancy is a condition that can affect the optimization of the mother and the fetus during pregnancy faced. Pregnant women at risk are pregnant women who have a greater risk or hazard at the time of pregnancy or delivery, compared to normal pregnant women. This study aimed to determine the effect of maternal characteristics (age, education) and knowledge on attitudes about high-risk pregnancies in the working area of Tanjung Beringin, Public Health Center, Hinai Subdistrict, Langkat District in 2012. This was descriptive analytic study with cross-sectional approach. The populations were all first trimester pregnant women as many as 54 mothers. The samples were the entire population as many as 54 mothers. The results showed that the direct effect of maternal age on the knowledge about high-risk pregnancies as many as 32.9%. Age contributed directly to the mother’s attitude on high risk pregnancy about 10,0%. Meanwhile, age contributed indirectly to the mother’s attitude on high risk pregnancy through the knowledge about 24,6%. Totally it contributed 14,6%. Education contributed directly to the mother’s knowledge on high risk pregnancy  about 20,0%. Both direct and indirect effect of education on mother’s attitude on high risk pregnancy trough knowledge about 14,9% and totally it contributed about 29,8%. The mother’s knowledge contributed  to the mother’s attitude on high risk pregnancy about 74,7%. From the results of the study, it is suggested that health personels can increase mother’s knowledge about high-risk pregnancies especially through health promotion efforts such as health education and providing  media of  information sources related to high-risk pregnancy. Keywords: Characteristics (Age, Education), Knowledge, Attitude, Pregnancy, High Risk Pregnancy